2022
DOI: 10.1001/jamanetworkopen.2022.7287
|View full text |Cite
|
Sign up to set email alerts
|

Association of Psychiatric Disorders With Incidence of SARS-CoV-2 Breakthrough Infection Among Vaccinated Adults

Abstract: Key Points Question Are psychiatric disorders associated with an increased risk for SARS-CoV-2 breakthrough infection after vaccination? Findings In this cohort study of 263 697 fully vaccinated US Department of Veterans Affairs patients, psychiatric disorder diagnoses were associated with increased incidence of SARS-CoV-2 breakthrough infection after vaccination. Meaning This study suggests that targeted strategies for preventin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 33 publications
4
20
0
Order By: Relevance
“…Currently, there are very few studies on mRNA vaccine efficacy in patients with SPI in treatment with psychotropic drugs. However, increased breakthrough infections and limited vaccine responses were reported by a recent epidemiological study on veterans with SPI, highlighting possible drug-vaccine interaction (Nishimi et al, 2022). This study is in line with earlier data, showing that, in general, patients with SPI exhibit suboptimal vaccine effectiveness, a phenomenon also documented in the geriatric population (Solomon et al, 1970;Hussar et al, 1971;Della Bella et al, 2007;Derhovanessian and Pawelec, 2012;Wang et al, 2016).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Currently, there are very few studies on mRNA vaccine efficacy in patients with SPI in treatment with psychotropic drugs. However, increased breakthrough infections and limited vaccine responses were reported by a recent epidemiological study on veterans with SPI, highlighting possible drug-vaccine interaction (Nishimi et al, 2022). This study is in line with earlier data, showing that, in general, patients with SPI exhibit suboptimal vaccine effectiveness, a phenomenon also documented in the geriatric population (Solomon et al, 1970;Hussar et al, 1971;Della Bella et al, 2007;Derhovanessian and Pawelec, 2012;Wang et al, 2016).…”
Section: Introductionsupporting
confidence: 89%
“…On the other hand, unlike older individuals, SPI patients display an increased number of natural killer cell (NKC) that are unaffected by the psychotropic drugs, probably explaining the low prevalence of malignancy as well as COVID-19 critical illness in this population (Yovel et al, 2000;Bao et al, 2021;Tarantino et al, 2021). Indeed, immune malfunction may account for both limited vaccine responses and protection from COVID-19 critical illness in medicated SPI patients (Nishimi et al, 2022), (Sfera et al, 2021;Nemani et al, 2022). For example, upregulated NKCs may promptly eliminate not only virus-infected but also mRNAtransfected cells, disrupting translation at the ribosomal level as well as antibody production (Arai et al, 1983;Brieva et al, 1984;Mason et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a population based study of individuals who received two doses of ChAdOx1 ( n = 5770) or BNT162b2 ( n = 3331) failed to demonstrate a significant effect of depression/anxiety (considered as a single category) on the presence or absence of anti-spike protein antibodies [ 178 ]. Another study of over a quarter of a million individuals found that people with any psychiatric disorder were at an increased risk of a breakthrough COVID-19 following vaccination with an OR of 1.03–1.07 depending on the statistical model [ 179 ]. For MDD, the relative risk ranged from 1.05–1.11 but for both MDD and other psychiatric disorders, the effect was strongest in the participants aged 65 years or more even after controlling for medical comorbidity [ 179 ].…”
Section: Covid-19 Vaccine Response and Mental Healthmentioning
confidence: 99%
“…Another study of over a quarter of a million individuals found that people with any psychiatric disorder were at an increased risk of a breakthrough COVID-19 following vaccination with an OR of 1.03–1.07 depending on the statistical model [ 179 ]. For MDD, the relative risk ranged from 1.05–1.11 but for both MDD and other psychiatric disorders, the effect was strongest in the participants aged 65 years or more even after controlling for medical comorbidity [ 179 ]. As with COVID-19 pathology, exactly which pre-existing immune phenotypes predict vaccine immunogenicity or efficacy have not been fully investigated.…”
Section: Covid-19 Vaccine Response and Mental Healthmentioning
confidence: 99%
“…10 Importantly, emerging studies suggested a diagnosis of psychiatric disorders increased risk factors for mortality in patients with COVID-19 and increased incidence of SARS-CoV-2 breakthrough infection after vaccination. 11,12 Evidence on the short-and longterm changes in psychiatric disorders is important to guide future targeted efforts on most at-risk populations.…”
Section: Introductionmentioning
confidence: 99%